Rearing Hoven’s Carp (Leptobarbus hoevenii) by Feeding Fermented With Herbal Supplements in a Recirculation System - Haris, Abdul; Putra, Iskandar; Rusliadi, Rusliadi (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2023)
Study aims to determine the best dose in rearing hoven’s carp (Leptobarbus hoevenii) by feeding fermented feed with herbal supplements in a recirculation system. This research was conducted from 16 January - 24 February 2022 at the UPT Experimental Pond of the Faculty of Fisheries and Marine Scnie, University of Riau. The container used was a black tub with a volume of 100 L as many as 15 units with a stocking density of 20 individuals / 80 L. This study used a one-factor completely randomized design (CRD) method with five levels of treatment and three replications. The level of treatment applied in this study was P0= without giving herbal supplements (control), P1 = doses of herbal supplements 100 ml / kg of feed, P2 = doses of herbal supplements 200 ml / kg of feed, P3 = dose of herbal supplements 300 ml/kg of feed and P4 = doses of herbal supplements 400 ml/kg of feed. The results showed that giving herbal supplements to feed with different doses had a significant effect (P <0.05) on growth but had no significant effect (P> 0.05) on the survival of leptobarbus hoevenii. The best treatment was found at the herbal supplement dosage of 300 ml/kg of feed, which resulted in absolute weight growth (5.52 g), absolute length growth (4.55 cm), specific growth rate (2.92 %), feed conversion ratio (1.80), survival rate (100%), feed digestibility (63.77%) , protein digestibility (80.16%).